On the Role of the Patella, ACL and Joint Contact Forces in the Extension of the Knee - Cleather,DJ; Southgate,DFL; Bull,AMJ (PLoS ONE, 2014)
Traditional descriptions of the knee suggest that the function of the patella is tofacilitate knee extension by increasing the moment arm of the quadriceps muscles.Through modelling and evidence from the literature it is shown in this paper that thepresence of the patella makes the ability of the quadriceps to rotate the thighgreater than their ability to rotate the tibia. Furthermore, this difference increases asthe knee is flexed, thus demonstrating a pattern that is consistent with many humanmovements. This paper also shows that the anterior cruciate ligament plays apreviously unheralded role in extending the shank and that translation at thetibiofemoral and patellofemoral joints is important in improving the capacity for thighrotation when the knee is flexed. This study provides new insights as to how thestructure of the knee is adapted to its purpose and illustrates how the functionalanatomy of the knee contributes to its extension function.